Manipulating the gut microbiome to alleviate steatotic liver disease: current progress and challenges - Saenz, Ernesto; Montagut, Nathally Espinosa; Wang, Baohong; Stein-Thöringer, Christoph; Wang, Kaicen; Weng, Honglei; Ebert, Matthias; Schneider, Kai Markus; Li, Lanjuan; Teufel, Andreas (Engineering, 2024)
The prevalence of metabolic-dysfunction-associated steatotic liver disease (MASLD) is alarmingly high; it is estimated to affect up to a quarter of the global population, making it the most common liver disorder worldwide. MASLD is characterized by excessive hepatic fat accumulation and is commonly associated with comorbidities such as obesity, dyslipidemia, and insulin resistance; however, it can also manifest in lean individuals. Therefore, it is crucial to develop effective therapies for this complex condition. Currently, there are no approved medications for MASLD treatment, so there is a pressing need to investigate alternative approaches. Extensive research has characterized MASLD as a multifaceted disease, frequently linked to metabolic disorders that stem from dietary habits. Evidence suggests that changes in the gut microbiome play a fundamental role in the development and progression of MASLD from simple steatosis to steatohepatitis and even hepatocellular carcinoma (HCC). In this review, we critically examine the literature on the emerging field of gut-microbiota-based therapies for MASLD and metabolic-dysfunction-associated steatohepatitis (MASH), including interventions such as fecal microbiota transplantation (FMT), probiotics, prebiotics, short-chain fatty acids, antibiotics, metabolic pathway targeting, and immune checkpoint kinase blockade.